2009
DOI: 10.1103/physrevb.80.033406
|View full text |Cite
|
Sign up to set email alerts
|

First-principles analysis of lattice thermal conductivity in monolayer and bilayer graphene

Abstract: Using calculations from first principles, we investigate the lattice thermal conductivity of ideal monolayer and bilayer graphenes. Our result estimates that the intrinsic thermal conductivity of both materials is around 2200 W m −1 K −1 at 300 K, a value close to the one observed theoretically and experimentally in graphite along the basal plane. It also illustrates the expected T −1 dependence at higher temperatures. The little variation between monolayer and bilayer thermal conductivities suggests that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
146
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(169 citation statements)
references
References 17 publications
18
146
2
Order By: Relevance
“…Our calculated phonon dispersion agrees with previous results [21][22][23][24][25], whereas the lattice thermal conductivity shows quantitative agreement with recent experimental data [26].…”
Section: Introductionsupporting
confidence: 82%
“…Our calculated phonon dispersion agrees with previous results [21][22][23][24][25], whereas the lattice thermal conductivity shows quantitative agreement with recent experimental data [26].…”
Section: Introductionsupporting
confidence: 82%
“…A calculation for bilayer graphene confirmed that the number of layers has little effect on the in plane thermal con ductivity, assuming no anharmonicity change. [97] In contrast, when Kn ≈ 1, most of the phonons will interact with other phonons and defects. [94] Thus, diffusion at the slab edge causes a reduction in the thermal conductivity.…”
Section: Transport Mechanisms In Bulk Materials With 2d Structuresmentioning
confidence: 99%
“…On the theoretical side, fundamental problems concerning the details of thermal transport in graphene have been subjects of debate [17][18][19][20][21][22][23][24][25][26][27][28][29][30], including the convergence behavior of k with system size, the extent of the diffusive and ballistic transport regimes, the role of flexural acoustic (ZA) phonons for thermal transport and strain effects on the convergence of k. It is generally believed that acoustic phonons [31] dominate the thermal transport in graphene. Based on this, 2D models give a logarithmic divergence with system size [27] but neglect the contributions from ZA phonons due to their low group velocities near the center of first Brillouin zone (FBZ) and their large Grüneisen parameters [32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, intensive efforts have been committed to understand the underlying thermal transport physics in graphene experimentally [1,[5][6][7][8][9][10][11][12][13][14][15][16] and theoretically [2,[17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%